Integration of UAV Photogrammetry and GIS in High-Resolution Topographic Mapping of Kedungsari Village, Temayang Subdistrict - Rendra, Mrabawani Insan; Adivin, Ahmad; Hadi, Arya Kusuma (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2025)
This study aims to acquire photogrammetric data for the purpose of generating a slope map of Kedungsari Village. Aerial imagery was captured using a drone flown at a specific altitude with optimal overlap and sidelap settings. To enhance positional accuracy, ground control points (GCP) were established and surveyed using the static method of Geodetic GPS. The data processing workflow involved photo alignment, georeferencing, dense point cloud generation, point cloud classification, digital elevation model (DEM) creation, and orthomosaic generation. The slope map was derived from a Digital Terrain Model (DTM), which was classified into several categories based on slope gradient. The resulting map is expected to serve as a reference for landslide susceptibility analysis and land-use planning